226k views
2 votes
Can you help me step by step

Can you help me step by step-example-1

1 Answer

7 votes

Answer:

n = -7

Explanation:

n - 7/4 = 35/12 + 5/3n

subtract n from both sides of the equation:

-7/4 = 35/12 + 2/3n

convert -7/4 to -21/12:

-21/12 = 35/12 + 2/3n

add 21/12 to both sides:

0 = 56/12 + 2/3n

convert 2/3n to 8/12n:

0 = 56/12 + 8/12n

subtract 56/12 from each side:

8/12n = -56/12

multiply both side by 12:

8n = -56

divide both sides by 8:

n = -7

User Bertday
by
5.6k points